DESIGN AND IMPLEMENTATION OF WEB BASED INFORMATION SYSTEM FOR THE THESIS DEFENSE SCHEDULE AND ASSESSMENT - Kana Saputra S; Insan Taufik; Debi Yandra Niska (Sean Institute, 2021)
Implementation of information system of academic especially in scheduling and assessment for online thesis defense is needed. This is because the implementation of thesis defense must be carried out online to avoid the possibility of spreading Covid-19. Therefore, The aims of this study to develop web-based information system for the thesis defense schedule and assessment. The development of information systems uses the waterfall model which consists of 5 steps are user requirement, system design, development, testing, and maintenance. The result of implementation show that web-based information system for the thesis defense schedule and assessment running well according to purpose and need assessment. The information system also can used for interaction between lecturers and students as long as the thesis process and defense don’t need to be done offline.